Electromagnetic transient characteristics and overvoltage suppression strategy of renewable energy-oriented power system connected by gas-insulated transmission lines - Yang, Guang; Zhu, Yong; Zen, Fanxing; Zhou, Shengzhi; Chen, Yuhang (Frontiers in Energy Research, 2022)
New energy systems, such as wind power and photovoltaic and distributed power supply, in the power generation and grid-connected transmission system basically will use stronger insulation design, higher operational safety, and smaller footprint GIL equipment, while the new energy transmission system of the smart grid development trend requires accompanying the electronic transformer equipment to promote a large area. However, the current GIL equipment used in new energy transmission systems has caused great electromagnetic interference to the electronic equipment due to the compact layout of the equipment and the transient signals generated by normal operation, which has seriously restricted the development of smart grids and became a major obstacle to the grid connection of new energy systems. In order to study the characteristics and developmental law of transient electromagnetic interference signal of GIL equipment in new energy transmission and transformation system, this study proposes a dynamic arc model based on an optimized arc extinguishing criterion, verifies the correctness of the improved dynamic arc model through theoretical analysis, simulates calculation combined with the test measurement data, and compares and analyzes the simulation results with test measurement data to study the transient electromagnetic interference source signal during arc burning duration. The simulation results and test data are compared and analyzed to study the pulse steepness, size of the wave head, and overall waveform development law of the transient electromagnetic interference source signal during the arc burning process. It is concluded that the dynamic arc model based on the optimized arc extinguishing criterion can be better used to study the transient electromagnetic interference signal in the GIL equipment. Meanwhile, the transient electromagnetic interference signal has the characteristics of large amplitude and high frequency, the maximum overvoltage can reach 1.9 p.u., the UHF can reach 30 MHz, and the wave head rise time is about 12 ns. This study provides theoretical support for subsequent research on suppressing transient electromagnetic interference source signals, improving the anti-electromagnetic interference performance of electronic devices, and is dedicated to solving the obstruction problem in the process of grid connection of new energy transmission and substation systems.